Selection of a minimal number of significant porcine snps by an information gain and genetic algorithm hybrid model - Rathasamuth, Wanthanee; Pasupa, Kitsuchart; Tongsima, Sissades (My University, 2019)
A panel of a large number of common Single Nucleotide Polymorphisms (SNPs) distributed across an entire porcine genome has been widely used to represent genetic variability of pigs. With the advent of SNP-array technology, a genome-wide genetic profile of a specimen can be easily observed. Among the large number of such variations, there exists a much smaller subset of the SNP panel that could equally be used to correctly identify the corresponding breed. This work presents a SNP selection heuristic that can still be used effectively in the breed classification. The features were selected by combining a filter method and a wrapper method-information gain method and genetic algorithm-plus a feature frequency selection step, while classification used a support vector machine. We were able to reduce the number of significant SNPs to 0.86 % of the total number of SNPs in a swine dataset with 94.80 % classification accuracy.
Keywords: Bioinformatics; Feature selection; Genetic algorithm; Information gain; Single nucleotide polymorphisms; Support vector machine; Swine